Regimes of representation in Canadian police museums: othering, police subjectivities, and gunscapes - Pauls, Haley (Crime, media, culture, 2023)
There are dozens of public police museums located across Canada that memorialize the country?s history of law enforcement and criminalization. Drawing from fieldwork at these sites, we explore the representational devices used to curate police museum displays. Invoking Stuart Hall?s work on representation and Othering, we examine how gun displays at Canadian police museums are organized to minimize the harm that police interventions with guns cause. Arguing these displays are made intelligible through a regime of representation that naturalizes the distinction between police officers and the ?criminal? Other, we examine how these museums position weaponry including the gun as an esthetic object and a force of social good when in the hands of police. Analyzing curatorial strategies such as the arrangement of weapons, mannequin placement, dress, and level of humanization, as well as the rhetoric and narratives espoused on accompanying placards, we show how the curatorial approach in these spaces ratify an ideological framework that normalizes police violence and criminalization. We then assess what our analysis contributes to literatures on police museums and policing myths.